2014
DOI: 10.4324/9780203111468
|View full text |Cite
|
Sign up to set email alerts
|

Managing Performance Abroad

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 1 publication
(1 reference statement)
1
48
0
2
Order By: Relevance
“…Such theorizing draws attention to the adjusting individual's social or professional "fit" with prominent exchange partners as an important determinant of their adjustment trajectory, rather than-or as well as-their "fit" with the overall physical or social environment (Shaffer et al, 1999). This perspective is consistent with calls to acknowledge the importance of different domains within which adjustment transpires (Haslberger et al, 2014) and with suggestions that adjusting to some aspects of a new culture (e.g., macro/micro) may be more difficult than others (Hippler et al, 2018). Our model, therefore, helps to progress the evolution of adjustment away from being viewed as assimilation to a static and essentialist macro-level milieu to one emerging from individuals' participation in a multiplicity of rich intercultural interactions, each taking place within a particular context and each shaping an individual's adjustment patterns in different ways.…”
Section: Research Implicationsmentioning
confidence: 85%
“…Such theorizing draws attention to the adjusting individual's social or professional "fit" with prominent exchange partners as an important determinant of their adjustment trajectory, rather than-or as well as-their "fit" with the overall physical or social environment (Shaffer et al, 1999). This perspective is consistent with calls to acknowledge the importance of different domains within which adjustment transpires (Haslberger et al, 2014) and with suggestions that adjusting to some aspects of a new culture (e.g., macro/micro) may be more difficult than others (Hippler et al, 2018). Our model, therefore, helps to progress the evolution of adjustment away from being viewed as assimilation to a static and essentialist macro-level milieu to one emerging from individuals' participation in a multiplicity of rich intercultural interactions, each taking place within a particular context and each shaping an individual's adjustment patterns in different ways.…”
Section: Research Implicationsmentioning
confidence: 85%
“…At the same time, it would be interesting to explore if Portuguese emerging adult SIEs in different host countries perceive cross-cultural adaptation and its determinants the same way as the ones in this study. By following these suggestions, it will be a step forward into changing the current situation of having “a wealth of indicators but a dearth of replications” (Haslberger et al , 2014, p. 129).…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion will hopefully address González-Loureiro et al .’s (2015) concern about how adjustment-acculturation have been researched as mutually exclusionary realms and scholars have devoted little effort to join the analyses. Nonetheless, since international assignments are becoming a more common practice in the increasingly globalized world (Haslberger et al , 2014), individuals seem to deal with three major concerns: work, the place where they live and the place where their family lives. Consequently, two or more cultures may be interacting and the individual has to decide the best way to deal with them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of homesickness has long been a neglected area of investigation in international human resource management. This is despite acceptance in the literature that expatriates go through the critical issue of adjustment (Haslberger et al, 2014) triggers the feelings of separation and missing home, and has been a not-easy-to-achieve situation (Ward et al, 2005). Cross-cultural research has identified significant ties between the cultural environment and human psychosocial development where examinations focus on what ends up happening to individuals who have grown in one cultural background in an effort to recreate their lives in another (Berry, 1997).…”
Section: Introductionmentioning
confidence: 99%